Safe Use of Infliximab for the Treatment of Severe Perianal Crohn's Disease After Diagnosis and Treatment of Lymphoma - Bernardes, C (2018)
Inflammatory bowel disease is associated with an increased likelihood of developing lymphoma. However, it is still controversial if this risk may be attributed to the disease itself or rather represents an effect of immunosuppressive treatment. Although tumor necrosis factor alpha (TNFα) is a key cytokine for cancer immunosurveillance, the potential relationship between anti-TNFα agents and the pathogenesis of lymphoproliferative disorders remains unclear. Here, we describe the case of a patient with severe perianal Crohn's disease, treated with infliximab monotherapy, whose unusual presentation with acute groin pain required surgical intervention and led to the diagnosis of diffuse large B-cell lymphoma. However, 10 months after this episode, treatment with infliximab was restarted because the patient continued with refractory and disabling perianal disease. Currently, with a follow-up of 36 months, under infliximab 10 mg/kg every 4 weeks, he maintains mild perianal Crohn's disease and persists in sustained clinical and imaging remission of the lymphoproliferative disorder.